2001
DOI: 10.1038/sj.gt.3301485
|View full text |Cite
|
Sign up to set email alerts
|

In vivo gene delivery into ocular tissues by eye drops of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) (PEO-PPO-PEO) polymeric micelles

Abstract: The primary objective of this study was to investigate the feasibility of using PEO-PPO-PEO non-ionic copolymeric micelles as a carrier for eye-drop gene delivery of plasmid DNA with lacZ gene in vivo. Using pyrene fluorescence probe methods, zeta potential, and dynamic light scattering test (DLS), the ability of micelle formation of these block copolymers with plasmid was studied. Gene expressions were visualized by both the quality of enzymatic color reaction using X-gal staining and by the quantification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 18 publications
1
88
0
1
Order By: Relevance
“…The core-shell structure may notably enhance the apparent aqueous solubility, leading to a greater concentration gradient favourable for diffusion, and also provide sustained release since the dilution factor in the lachrymal fluid is less than in other administration routes [16]. Polymeric micelles have been shown to be suitable ocular carriers for anti-inflammatory drugs [17] or even plasmids and genes [18,19]. Transcorneal permeation studies through excised rabbit cornea indicated that non-steroidal anti-inflammatory drug formulations in polymeric micelles can enhance about twofold drug permeation compared with that of an aqueous suspension of the same concentration because the dissolution step is overcome [17].…”
Section: Introductionmentioning
confidence: 99%
“…The core-shell structure may notably enhance the apparent aqueous solubility, leading to a greater concentration gradient favourable for diffusion, and also provide sustained release since the dilution factor in the lachrymal fluid is less than in other administration routes [16]. Polymeric micelles have been shown to be suitable ocular carriers for anti-inflammatory drugs [17] or even plasmids and genes [18,19]. Transcorneal permeation studies through excised rabbit cornea indicated that non-steroidal anti-inflammatory drug formulations in polymeric micelles can enhance about twofold drug permeation compared with that of an aqueous suspension of the same concentration because the dissolution step is overcome [17].…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed the ability of PEO-PPO-PEO polymeric micelles to deliver plasmid DNA with lacZ gene in vivo [26]. After topical administration three times a day for 2−3 days, enhanced gene expression was observed in the iris, sclera, conjunctiva and lateral muscle of rabbit eyes.…”
Section: Polymeric Micellesmentioning
confidence: 95%
“…Currently, most light sensitive systems for drug and gene delivery are administered intravenously; however, techniques to administer PEO-PPO-PEO non-ionic copolymeric micelles through topical eye drops have shown promise in ocular tissues [26]. The study revealed the ability of PEO-PPO-PEO polymeric micelles to deliver plasmid DNA with lacZ gene in vivo [26].…”
Section: Polymeric Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advances made in the gene delivery field, to our knowledge, there are no reports in the literature on the potential of nanoparticles, presented as liquid eye drops, for the transport of genes across the ocular barrier, although other synthetic vectors such as micelles and liposomes have shown a certain potential for this specific application. 40,41 Given the positive results obtained in the present work in terms of the ability of HA-CS nanoparticles to transfect differentiated cells and to enter the ocular epithelia, we further explored in vivo their potential in ocular gene therapy. Nanoparticles loaded with pEGFP or pbgal were administered onto the eye surface, and the cornea and conjunctiva were evaluated for gene expression.…”
Section: Bioadhesive Nanoparticles For Ocular Gene Therapy M De La Fumentioning
confidence: 99%